Concentration Study of a Specularite Ore via Shaking Table, Reverse Flotation, and Microwave-Assisted Magnetic Separation - Al-Dhubaibi, Ammar Mahdi Ahmed; Vapur, Huseyin; Top, Soner; Sivrikaya, Osman (Taylor & Francis inc, 2022)
Despite the difficulties in pelletizing specularite-type refractory iron ores, the utilization of these resources is indispensable for the steel industry due to the increasing need for iron. This study investigated Fe recovery from a refractory iron ore using gravity separation, reverse flotation, and two-stage magnetic separation. Tilt angle and particle size had a significant effect on the grade and recovery of concentrates in shaking table tests. Gravity concentration at optimum conditions resulted in an iron concentrate with 64.47% Fe grade and 90.73% Fe recovery. In the reverse flotation tests, the frother and depressant substantially affected the Fe grade of concentrates while the collector influenced the Fe recovery. A 90% Fe recovery with 64.69% Fe grade was obtained within optimum flotation conditions. The Fe grades were raised to >67.5% in products after the first magnetic separation. The tailings of the first magnetic separation were subjected to the second magnetic separation after microwave-assisted roasting to increase the magnetic susceptibility. In the second magnetic separation, a concentrate containing 66.06% Fe was separated from the microwave-roasted non-magnetic material with 82.23% Fe recovery. To the best of our knowledge, the microwave-roasting method has been applied to a specularite-type refractory iron ore for the first time.
Al-Dhubaibi, Ammar Mahdi Ahmed/0000-0001-9301-752X; Top, Soner/0000-0003-3486-4184
Keywords: Iron Ore; Shaking Table; Flotation; Magnetic Separation; Upgrade